Solar and electric irrigation system in kinnow orchard of Rajasthan: Comparative evaluation - MEENA, N K; SINGH, RAM; FEROZE, S M (The Indian Journal of Agricultural Sciences, 2021)
The photo voltaic (PV) solar device for pumping water from underground and from other source of water for irrigation has been recognized as very new initiative. Three year (2015-18) socio-economic study sponsored by Ministry of Human Resource under higher education scheme has been conducted in two districts, viz. Sri Ganganagar and Bikaner of Rajasthan applying standard methodology to assess comparative advantages of PV solar device for irrigation of kinnow orchard. Hence, study found that solar irrigation system has enhanced the returns of farm and played a partial catalyst role to enhance the income of the farm. Therefore, the economic as well as environment benefits need to realizefor popularization the solar device for betterment of farming society which would reduce the dependency on electricity of farmers for irrigation specially and other works depend on electricity generally. Hence, provision of incentives on solar devices should be made to the farmers.